Vemurafenib Induces Senescent Phenotype with Increased Adhesion in BRAF Mutant A375 but not in Wild Type BRAF SK-MEL-2 Melanoma Cells - Aleksandra Rashidovna Esimbekova; Vasiliy Dmitrievich Belenyuk; Andrey Anatolievich Savchenko; Tatiana Gennadievna Ruksha (Advanced Pharmaceutical Bulletin)
Purpose: The present study aimed to determine the selective effects of BRAF V600E inhibitor on focal adhesion in melanoma cells with respect to their phenotypic reprogramming. Methods: Flow cytometry was used to analyse the distribution of BRAFV600E and BRAFWT melanoma cells throughout the cell cycle post-vemurafenib treatment. Senescent cells were identified based on b-galactosidase activity and the mRNA expression of cell cycle proteins, CCND1 and RBL1. Centrifugal cell adhesion assay was used to determine the adhesive capacities of resting and proliferative BRAF mutant and BRAF wild-type melanoma cells under vemurafenib treatment. Fibronectin binding was evaluated by spectrophotometry and quantitative real-time PCR to measure the mRNA levels of integrins: ITGAV, ITGA5, ITGB1 and ITGB3. Results: Vemurafenib increases the proportion of melanoma BRAFV600E-positive cells in the G0 phase of a cell cycle. Melanoma cells entering the G0 phase after vemurafenib treatment indicated an upregulation of senescence-associated markers. Non-proliferating melanoma cell number was elevated among vemurafenib-treated BRAFV600E cells with enhanced attachment. BRAFV600E-positive but not BRAFV600E-negative cells were characterised by upregulated ITGAV. Conclusion: The current results demonstrated that vemurafenib induces the phenotypic switch in melanoma cells depending on their mutational status. It also strengthens the adhesive features of senescent cells, increasing their binding to fibronectin via ITGAV, which may be a part of the phenotypic mode of drug resistance or slow interaction of proliferating cancer cells with the extracellular matrix (ECM). Thus, targeting senescent cells by focal adhesion modulators may be a promising approach to control drug-resistant melanoma cells.